Truncated DNMT3B isoform DNMT3B7 suppresses growth, induces differentiation, and alters DNA methylation in human neuroblastoma - Ostler, Kelly R. (2012)
Epigenetic changes in pediatric neuroblastoma may contribute to the aggressive pathophysiology of this disease, but little is known about the basis for such changes. In this study, we examined a role for the DNA methyltransferase DNMT3B, in particular, the truncated isoform DNMT3B7 which is generated frequently in cancer. To investigate if aberrant DNMT3B transcripts alter DNA methylation, gene expression, and phenotypic character in neuroblastoma, we measured DNMT3B expression in primary tumors. Higher levels of DNMT3B7 were detected in differentiated ganglioneuroblastomas compared to undifferentiated neuroblastomas, suggesting that expression of DNMT3B7 may induce a less aggressive clinical phenotype. To test this hypothesis, we investigated the effects of enforced DNMT3B7 expression in neuroblastoma cells, finding a significant inhibition of cell proliferation in vitro and angiogenesis and tumor growth in vivo. DNMT3B7-positive cells had higher levels of total genomic methylation and a dramatic decrease in expression of the FOS and JUN family members that comprise AP1 transcription factors. Consistent with an established antagonistic relationship between AP1 expression and retinoic acid receptor activity, increased differentiation was seen in the DNMT3B7-expressing neuroblastoma cells following treatment with all-trans retinoic acid (ATRA) compared to controls. Our results indicate that DNMT3B7 modifies the epigenome in neuroblastoma cells to induce changes in gene expression, inhibit tumor growth, and increase sensitivity to ATRA.